2016
DOI: 10.1038/pj.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of branching position of alkyl side chains on ordering structure and charge transport property in thienothiophenedione- and quinacridone-based semiconducting polymers

Abstract: To investigate the effect of the branching position of the alkyl groups on the side chain of semiconducting polymers, we synthesized two series of semiconducting polymers based on thienothiophene-2,5-dione (PTTD4Ts) and quinacridone (PQA2Ts). 2-Decyltetradecyl, 3-decylpentadecyl, 4-decylhexadecyl, and 5-decylheptadecyl groups were used, and the branching position was systematically varied from the second carbon from the backbone to the fifth carbon. These branched side chains are introduced into the thiophene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…A comparison of the crystalline structures of PQCQT and PQCTQx in film state revealed that the crystalline structure of PQCTQx was not as good as that of PQCQT for charge transport in OFET devices [17,18]. Because the diphenylquinoxaline unit in PQCTQx is in bulky groups and generates steric hindrance, edge-on arrangement may become difficult [19,20]. Increasing the annealing temperature by an additional 50 °C yielded decreased intensities of the observed peaks along both (100) and (010) directions.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the crystalline structures of PQCQT and PQCTQx in film state revealed that the crystalline structure of PQCTQx was not as good as that of PQCQT for charge transport in OFET devices [17,18]. Because the diphenylquinoxaline unit in PQCTQx is in bulky groups and generates steric hindrance, edge-on arrangement may become difficult [19,20]. Increasing the annealing temperature by an additional 50 °C yielded decreased intensities of the observed peaks along both (100) and (010) directions.…”
Section: Resultsmentioning
confidence: 99%
“…However, this is not always coupled to an increased charge carrier mobility as measured in organic field‐effect transistors. The alkyl chain can also influence the preferred orientation (edge‐on versus face‐on) of the π‐conjugated main chain with respect to the substrate after depositing the polymers from solution [6, 7, 9] …”
Section: Introductionmentioning
confidence: 99%
“…With their interesting optical and electrical properties, organic semiconductors are increasingly prominent in various electronic devices such as organic photovoltaics (OPVs) [1][2][3][4][5][6][7][8][9] and organic thin lm transistors (TFTs). [10][11][12][13][14][15][16][17][18] In particular, due to their solution processability and mechanical exibility, organic semiconductors would become fundamental components for novel mobile electronic devices, such as exible displays, biocompatible sensors, and radio frequency identication (RFID) tags. [19][20][21] In order to realize such next-generation devices, signicant efforts have been devoted to the development of new organic semiconducting materials, some of which already demonstrated charge carrier mobilities beyond the benchmark of industry standard inorganic materials, such as amorphous silicon (0.1-1 cm 2 V À1 s À1 ).…”
Section: Introductionmentioning
confidence: 99%